Bulgaria : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Bulgaria. (IMF Staff Country Reports; Country Report ;, 2018)
This 2017 Article IV Consultation highlights that the Bulgarian economy is performing well. Growth has been on an upward trend and is estimated to reach 3.8 percent in 2017 and 2018, driven by strong exports, easier financial conditions, and growing confidence. The current account remained in surplus in 2017, despite rapid wage growth. The economy shows signs of a closing output gap. Headline inflation turned positive in 2017 and inflationary pressure is rising. Fiscal outcomes have been stronger than budgeted in recent years, reflecting mainly revenue overperformance and under-execution of capital spending. The main challenge is to translate this recent recovery into sustained and inclusive growth and convergence with other European Union countries.